Implementasi sila ke-4 pancasila dalam organisasi - shofianatus, dwi ari (Maliki Interdisciplinary Journal, 2026)
Pancasila, as the foundation of the Indonesian state, plays an essential role in regulating national life, including within organizational contexts. The fourth principle, “Democracy guided by the inner wisdom in the unanimity arising out of deliberations amongst representatives”, emphasizes democracy, deliberation, and representation as the basis for decision-making. This study aims to explain the concept of implementing the fourth principle in organizations, identify the challenges faced, and provide solutions to strengthen its application. The discussion shows that the implementation of the fourth principle can be realized through a culture of consensus deliberation, democratic leadership, fair representation systems, and transparency in decision-making. Challenges include low member participation, domination of elite interests, limited understanding of democratic values, and time constraints in deliberation processes. Efforts to overcome these challenges involve strengthening democratic education through leadership training, regular discussion forums, and fostering tolerance for differences of opinion. The conclusion highlights that applying the fourth principle of Pancasila in organizations creates a fair, open, and harmonious atmosphere, enabling organizations to reflect national values while strengthening integrity and solidarity.